2019
DOI: 10.24843/ejes.2019.v13.i01.p02
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS PENCEMARAN Cr(VI) DI SUNGAI BADEK, KOTA MALANG DENGAN MENGGUNAKAN BIOFILM

Abstract: One of the most severe environmental problems is heavy metal pollution such as Cr(VI) in aquatic ecosystems.  Cr(VI) is toxic and carcinogenic heavy metals pollutants that persistent and easily accumulated through the food web. Accumulation of Cr(VI) concentration in the aquatic ecosystem gradually increases with the increases of industrial activity. Therefore, Cr(VI) concentration in aquatic ecosystems should be monitored continuously, and thus, suitable and accuracy monitoring technologies are necessary. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…As Barnes and Vidgen (2000) stated, unreliable, inadequate, and inaccurate information can cause a decrease in customer trust in the online context and consequently hinders customer relationships. Kurniawan et al (2018) confirmed this notion. He found that website quality has a significant effect on trust.…”
Section: Resultssupporting
confidence: 57%
“…As Barnes and Vidgen (2000) stated, unreliable, inadequate, and inaccurate information can cause a decrease in customer trust in the online context and consequently hinders customer relationships. Kurniawan et al (2018) confirmed this notion. He found that website quality has a significant effect on trust.…”
Section: Resultssupporting
confidence: 57%